Collaborative Translation as a Teaching Technique to Improve Students’ Translation Ability - Yohana Puspita Dewi; Destia Herlisya; Purna Wiratno (STKIP PGRI Bandar Lampung, 2025)
This study was done to help students improve their translation skills by using Collaborative Translation. The students involved were third-semester students studying English Education at STKIP PGRI Bandar Lampung for the 2025/2026 academic year. There were 22 students in total. The research used Classroom Action Research, which had two cycles. To collect data, the researchers used both tests and non-tests. The tests included formative and summative assessments. For non-tests, they used observation sheets and field notes. When analyzing the data, they used both quantitative and qualitative methods. The results showed that Collaborative Translation was effective in improving students' learning activity and translation skills. The average score for learning activity went up from 6.37 in the first cycle to 7.50 in the second cycle, which means the students became more active. The average translation score increased from 57.5 in the first cycle to 70.22 in the second cycle. Therefore, using Collaborative Translation was successful in improving both the students' learning activity and translation skills at the third semester level in the English Education program at STKIP PGRI Bandar Lampung for the 2025/2026 academic year.